2021
DOI: 10.3390/ijms22041849
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor 2 As a Possible Neuroprotective Agent and Memory Enhancer—Its Comparative Expression, Processing and Signaling in Mammalian CNS

Abstract: A number of studies performed on rodents suggest that insulin-like growth factor 2 (IGF-2) or its analogs may possibly be used for treating some conditions like Alzheimer’s disease, Huntington’s disease, autistic spectrum disorders or aging-related cognitive impairment. Still, for translational research a comparative knowledge about the function of IGF-2 and related molecules in model organisms (rats and mice) and humans is necessary. There is a number of important differences in IGF-2 signaling between specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 300 publications
(639 reference statements)
3
15
0
Order By: Relevance
“…Third, the spatial domains detected by SpatialPCA allowed us to identify region specific markers that are not identified by other methods. For example, only SpatialPCA detected the enrichment of Itpka, Igfbp4 and Map4 in the CA1 region of the hippocampus, consistent with their known enrichment pattern in the hippocampus pyramidal neurons [53][54][55] (Figure 4e). Other marker genes that are highly expressed in the substructures of the hippocampus are shown in Figure 4d.…”
Section: Mouse Hippocampus Data By Slide-seq V2supporting
confidence: 74%
“…Third, the spatial domains detected by SpatialPCA allowed us to identify region specific markers that are not identified by other methods. For example, only SpatialPCA detected the enrichment of Itpka, Igfbp4 and Map4 in the CA1 region of the hippocampus, consistent with their known enrichment pattern in the hippocampus pyramidal neurons [53][54][55] (Figure 4e). Other marker genes that are highly expressed in the substructures of the hippocampus are shown in Figure 4d.…”
Section: Mouse Hippocampus Data By Slide-seq V2supporting
confidence: 74%
“…sAPPα (and BDNF) share some common functionalities with Insulin-like Growth Factor 2 (IGF2), and memory retention and LTP can be enhanced and ‘forgetting’ prevented by the addition of endogenous Insulin-like Growth Factor 2 (IGF2) [ 82 , 83 ]. A study analysing astrocyte protein secretion and gene expression in three mouse models of genetic neurodegenerative diseases (Rett, Fragile X and Down syndrome) showed that astrocytes secrete the IGF2 inhibitory protein IGFBP2, causing learning and memory failure [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Igf2 was increased after treatment with anti-C1-INH, and combined RT and anti-C1-INH compared to control. Igf2 has been demonstrated in the brain of rodents, possibly increased in hippocampus and neural stem cells [ 35 ]. Thbs1 was increased in all treated groups compared to control.…”
Section: Resultsmentioning
confidence: 99%